Pengembangan E-Modul Penggunaan Aplikasi Google Maps Berbasis Android pada Pembelajaran Tematik Tema 8 Subtema 4 - Lauzam Muruz; Maslikhah Maslikhah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
The need for third grade teachers at MI Nurul Islam and MI Darul Ulum is the development of e-modules using media or learning resources based on information and communication technology. There are no new innovations regarding Android-based teaching materials, media or learning resources in thematic learning of theme 8 sub-theme 4 for third grade. The purpose of this research is to develop an e-module using android-based google maps in thematic learning of theme 8 sub-theme 4 for third grade, in order to provide active learning and substantial experiences for students. This research is a development research with the ADDIE model, namely, analysis, design, development, implementation, and evaluation. Data analysis used a quantitative description approach through data collection using questionnaires, interviews and documentation techniques. The object of this research is an e-module using android-based google maps in thematic learning of theme 8 sub-theme 4, with product effectiveness as the benchmark variable. The need for an e-module using Android-based Google Maps comes from interviews with third grade teachers at MI Nurul Islam Semarang and MI Darul Ulum Semarang, who stated that there was no innovation in updating the E-module using Android-based Google Maps as active learning teaching materials. , so that it becomes the basis for research to make this research product. The form of the product in this study is an E-module using Android-based Google Maps as the program with the results of validation by a technology expert who gets a score of 95, and the value of a thematic material expert gets a score of 90. The effectiveness of this E-module can be seen from the average increase in field trials, which are divided into two stages. First limited trial with a score of 98.4. The second expanded trial got a score of 118.5. The conclusion of this research is that the e-module using Android-based Google Maps in thematic learning of theme 8 sub-theme 4 is needed in schools. The form of the development of this research is in the form of an e-module. The results of the e-module are effective for use in active learning.